2014
DOI: 10.1159/000368321
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Assisted Hydrophilization of Cochlear Implant Electrode Array Surfaces Enables Adhesion of Neurotrophin-Secreting Cells

Abstract: Objective: To evaluate plasma treatment for enhancing the biocompatibility of cochlear implant (CI) silicone surfaces, thus allowing colonization with human adipose-derived stem cells (hASCs) that are known to provide neurotrophic support. Methods: Silicone samples and CI electrode arrays were treated with 4 low-pressure plasmas of different characteristics. The hydrophilicity of plasma-treated and control surfaces as well as the adherence and morphology of hASCs were assessed. Finally, the insertion forces of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Both size and flexibility of the electrode array have an impact on the insertion forces. The insertion forces measured in a well‐established cochlea model of PD‐treated CIs with and without ASCs and untreated electrode arrays did not differ significantly in this experimental series, and the insertion forces determined by both types of electrode carriers were similar to those found in previous studies . Slightly decreased insertion forces were determined at insertion depth of 20 mm for PD‐coated CIs with cells.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Both size and flexibility of the electrode array have an impact on the insertion forces. The insertion forces measured in a well‐established cochlea model of PD‐treated CIs with and without ASCs and untreated electrode arrays did not differ significantly in this experimental series, and the insertion forces determined by both types of electrode carriers were similar to those found in previous studies . Slightly decreased insertion forces were determined at insertion depth of 20 mm for PD‐coated CIs with cells.…”
Section: Discussionsupporting
confidence: 80%
“…The insertion forces measured in a well-established cochlea model of PD-treated CIs with and without ASCs and untreated electrode arrays did not differ significantly in this experimental series, and the insertion forces determined by both types of electrode carriers were similar to those found in previous studies. 20,36 Slightly decreased insertion forces were determined at insertion depth of 20 mm for PD-coated CIs with cells. Fluorescence pictures of the PD-coated CIs with cells taken before and after insertion in the scala tympani model showed that only few cells were detached afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…A three-dimensional, porous collagen sponge is similar to the extracellular matrix, compatible with the human body, and an ideal microenvironment for adhesion, spread, and proliferation of ASCs or MG-63 cells [56]. Excellent biocompatibility which can be affected by many factors including drugs, microenvironment, or endocrine changes is a critical requirement for scaffolds in adipose tissue engineering [79]. …”
Section: Introductionmentioning
confidence: 99%
“…Image was taken when using a handheld plasma device based on piezoelectric direct discharge (PDD) technology. The gaseous plasma jet can be seen exiting the nozzle and spreading over the target surface CAP also endows mechanical improvement of surface, which enhances the adhesion and spreading of MSCs [13] Nitrogen plasma is better than oxygen and air plasma in improving MSCs attachment on gelatin scaffolds [14] CAP modification of PU scaffolds results in differential increments of cell attachment for ESCs and NSCs [15] Nanoscale, rather than microscale, PCL scaffolds attract larger benefits from CAP treatment for MSC adhesion [16] CAP-modified cochlear implant electrode array surface enables colonization of NT-secreting ASCs [17] Promoting stem cell proliferation…”
Section: Stem Cell Niche and Control Of Stem Cell Fatementioning
confidence: 99%
“…The relevant research priority has shifted in the last several years; the emerging applications use genetically modified stem cells. In the study performed by Schendzielorz et al, CAP-assisted hydrophilization of cochlear implant electrode array surfaces enabled firm colonization of human adipose-derived stem cells (ASCs) that are known to secrete neurotrophins [17]. This long-term delivery of neurotrophic factors has profound clinical potential for treating inner ear diseases and neurotology conditions.…”
Section: Stem Cell Niche and Control Of Stem Cell Fatementioning
confidence: 99%